Upaya Meningkatkan Hasil Belajar IPA Materi Kegunaan Energi dengan Metode Demonstrasi Siswa Kelas V SD Negeri 4 Muara Dua - Zubaidah Zubaidah (Keguruan, 2021)
The aims of this study are: (a) To improve the science learning outcomes (b) to increase the activeness of students in learning Science (c) to increase students' interest in learning Science? The research method used is classroom action research (CAR) that consists of 2 cycles. The subjects of Class V students as 26 students. Data analysis used comparative descriptive analysis techniques by comparing the initial conditions with the results achieved in each cycle, and qualitative descriptive analysis of observations by comparing the results of observations and reflections in cycle I and cycle II. The results showed a very significant increase in student achievement. In the initial test, it was obtained that 60% increased to 91.43% in the final test of the second cycle of action. It was concluded that through the demonstration method, it was possible to improve the learning outcomes of students in Class V Semester I of the science subject